Kesalahan Penulisan Tataran Morfologi Pada Teks Essay Siswa Kelas IX SMP Negeri 45 Medan - Futi Hamdiyah Telaumbanua; Fathiah Riadianti; Wulan Nurhasanah; Achmad Yuhdi; Anggia Puteri (CV. Alim's Publishing, 2024)
This research aims to explain language errors in the field of morphology in the essay texts of class IX students at SMP Negeri 45 Medan. This type of research is qualitative research using descriptive methods. The data source is in the form of essay texts from class IX students. The data collection technique in this research is documentation technique. Documentation techniques are used to collect data in the form of notes, transcripts, books, etc. The results of this research contained several errors, namely 10 errors in affixation, 8 errors in reduplication and 1 error in compounding.